Comparing the Socio-Economic Lives of Fishermen and Onion Farmers in West Sumatra - Robi Mitra; Indeska Putra (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2024)
This research aims to compare the socio-economic life of fishing communities with shallot farming communities. Research on fishing communities was carried out in 2023 in Nagari Sasak, West Pasaman Regency, and research on the lives of shallot farmers was carried out in Nagari Lolo, Solok Regency. This research was analyzed using socio-economic theory. The main components of socio-economic position include measures of wealth, measures of power, measures of honor, and measures of knowledge. This research uses a qualitative approach with a descriptive research type. The informants were selected using purposive sampling with a total of 30 informants (15 informants from the fishing community and 15 from the shallot farming community). Data collection was carried out using in-depth interviews, observation, and documentation. The results of this research can be concluded that: (1) Fishermen's income is uncertain and the sea is the only source of income, while shallot farmers have other sources of income, such as rice fields, bananas, and others (2) The living conditions of fishing communities are more in tiny wooden houses with cement floors, while many shallot farmers already have permanent houses with ceramic floors (3) The education level of fishing communities is generally middle school and high school, while many shallot farmers already have children with graduate degrees.